2017
DOI: 10.4103/0366-6999.204114
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Characteristics of Cortical Sulcus Development in the Human Fetus between 18 and 41 Weeks of Gestation

Abstract: Background:Fetal brain development is a complicated process that continues throughout pregnancy. Fetal sulcus development has typical morphological features. Assessment of fetal sulcus development to understand the cortical maturation and development by prenatal ultrasound has become widespread. This study aimed to explore a reliable method to assess cortical sulcus and to describe the normal sonographic features of cortical sulcus development in the human fetus between 18 and 41 weeks of gestation.Methods:A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 28 publications
0
18
0
1
Order By: Relevance
“…Excluded studies and reasons for exclusion are reported in Table S3 . Finally, 42 studies, reported between January 1970 and 2021, met the inclusion criteria, and these provided data for 45,626 fetuses, included in the final analysis ( Table 1 ) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The median sample size of participating fetuses was 372.5 (range: 50 to 8313; 25th percentile: 175.8; 75th percentile: 709.3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Excluded studies and reasons for exclusion are reported in Table S3 . Finally, 42 studies, reported between January 1970 and 2021, met the inclusion criteria, and these provided data for 45,626 fetuses, included in the final analysis ( Table 1 ) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The median sample size of participating fetuses was 372.5 (range: 50 to 8313; 25th percentile: 175.8; 75th percentile: 709.3).…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies reported more than one fetal brain structure [ 9 , 10 , 17 , 32 , 34 , 36 , 41 , 42 , 43 ]. In addition, 4 studies reported charts for POF [ 9 , 10 , 17 , 36 ], 6 for SF [ 9 , 10 , 17 , 35 , 36 , 44 ], 3 for AV [ 22 , 36 , 43 ], 14 for PV [ 7 , 8 , 14 , 19 , 23 , 26 , 27 , 30 , 32 , 34 , 36 , 38 , 40 , 43 ], 20 for TCD [ 12 , 15 , 16 , 18 , 20 , 21 , 24 , 25 , 28 , 31 , 32 , 34 , 39 , 41 , 42 , 43 , 45 ,…”
Section: Resultsmentioning
confidence: 99%
“…used transabdominal 3D multiplanar imaging and attempted to evaluate the Sylvian fissure. Thereafter, several articles have been published on the evaluation of the Sylvian fissure on neuroimaging. In a recent study by Hahner et al .…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that the development of the sylvian fissure, a landmark of gyration, can be identified on a 2D ultrasound from 16 gestational weeks onward [21,27]. Accordingly, an accurate grading of the time-dependent cortical folding for other primary fissures such as the parietooccipital fissure, calcarine fissure, and the cingulate sulcus is feasible with obligate visualization from 23 and 24 weeks onward [1,5]. There are also technical issues in the comprehensive assessment of the sylvian fissure in the same cutting plane and a lack of standardization in both plane reconstruction and the quantification of spatial-cerebral relationships [19].…”
Section: Discussionmentioning
confidence: 99%